2008
DOI: 10.1097/mao.0b013e3181845854
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Vestibular Testing in Patients With Vestibular Schwannoma Based on the Nerve of Origin, the Localization, and the Size of the Tumor

Abstract: 1) The nerve of origin of tumors cannot be predicted based on caloric response and VEMP. 2) In the intermediate and medial types, caloric response and the VEMP amplitude are significantly diminished in association with an increase in tumor size. 3) Prolonged VEMP latencies seem to be not only caused by tumor compression to the brainstem or vestibular spinal tract but also by tumor compression isolated to the inferior vestibular nerve.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
38
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(42 citation statements)
references
References 15 publications
2
38
2
Order By: Relevance
“…Previous histopathological studies have shown that >80% of the ganglions have to be lost before a shift in PTA threshold occurs, and that the loss of ganglions affects discrimination and PTA disproportionally [29] . Contrary to our results, other studies have shown a correlation between caloric hypofunction and size [5,11,21] . An explanation for the missing correlation in our study could be the relatively small size interval of tumors of which 91% had a diameter of 11-30 mm.…”
Section: Discussioncontrasting
confidence: 56%
See 3 more Smart Citations
“…Previous histopathological studies have shown that >80% of the ganglions have to be lost before a shift in PTA threshold occurs, and that the loss of ganglions affects discrimination and PTA disproportionally [29] . Contrary to our results, other studies have shown a correlation between caloric hypofunction and size [5,11,21] . An explanation for the missing correlation in our study could be the relatively small size interval of tumors of which 91% had a diameter of 11-30 mm.…”
Section: Discussioncontrasting
confidence: 56%
“…An explanation for the missing correlation in our study could be the relatively small size interval of tumors of which 91% had a diameter of 11-30 mm. This interval differs from the other studies that have a larger distribution of small tumors and a larger range of sizes [5,11] . In the present study, the medium and moderately large groups were similarly affected on all audiovestibular parameters (Table 2), which could indicate a ceiling effect on the loss of function for many tumors in this size range.…”
Section: Discussioncontrasting
confidence: 51%
See 2 more Smart Citations
“…However, with increasing size the vHIT might become pathological [69][70][71]. It is controversially discussed if UW is a predictor for tumour size [70,72] or not [73]. It was shown that the VOR gain of vHIT is not correlated with the tumour size [70] but rated together with the CI there was a correlation.…”
Section: Vestibular Schwannoma (Vs)mentioning
confidence: 94%